Alternative beta model in practice: the Brazilian fund industry case - Mendonça, Luisa Passebon (2021)
The present work introduces practical aspects into the alternative beta methodology in order to bring its implementation closer to a real life experience. The literature focus mostly on theoretical aspects with little attention to practical usage. The methodology developed in this work touches several practical aspects of the investment process in order to be closer to real life replication experience. We implemented the algorithm using the Kalman filter in order to replicate eight Brazilian Multimarket funds between January 2015 and December 2020. We were able to closely track and, in half of the period, even outperform the original funds while observing the impact of the real life details on the model performance.